Genetic Testing Consumers in Italy: A Preliminary Investigation of the Socio-Demographic Profile, Health-Related Habits, and Decision Purposes - Oliveri, Serena; Marton, Giulia; Vergani, Laura; Cutica, Ilaria; Gorini, Alessandra; Spinella, Francesca; Pravettoni, Gabriella (Frontiers in Public Health, 2020)
Aim of the study: Genetic testing is becoming increasingly common in clinical practice and health management; nonetheless, little is known about how the population approaches genetic services through private companies. Our study aims to describe socio-demographic aspects, health-related habits, and overall beliefs and knowledge about genetic risk and testing in a population of Italian citizens who decided to undergo a genetic examination through a private genetic company. Study design: A sample of 152 clients from an Italian private genetic company completed an ad-hoc survey from September 2016 to February 2018, addressing socio-demographic data, health habits, psycho-physic condition, perceived utility of genetic results, decision purposes about data sharing, and behavioral changes after results. Results: Participants (mean age 42.4) were predominantly female (82.2%) and were overall well-educated. Their main source of information were physicians (77%), and 41.1% entrusted the management of results to the same. Thirty-eight percentage underwent genetic analysis for cancer predisposition, 31.3% for fertility problems, 24% for dietary or intolerance issues in the period of enrolment. More than half of them (62.7%) reported a family history of the disease, and overall 69% had a current or past experience with a disease. Clients perceived the genetic screening as useful to adopt behaviors that may prevent disease onset (37.7%), to know their “real health status” (27.4%), and to adopt health-related behaviors (23.3%). 62.8% claimed they were motivated to change behaviors after results (healthier diet, practice exercise, medical checks), and they wanted to share results with their physician and family members. Discussion/Conclusion: The overview of consumers' profiles in Italy and other European countries can contribute to tailoring and regulating genetic services in a way that could be efficient in terms of healthy choices, behaviors, and health resource expenditures for the general public.